Chlamydia infection resembling ulcerative colitis: Case report - Palhares, Dario (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: The diagnosis of ulcerative colitis is relatively complex because the symptoms are similar to those seen in several other diseases. Objective: To report a case of rectal chlamydial infection whose initial symptoms resembled ulcerative colitis. Case report: A 50-year-old male patient presented with diarrhea, blood and mucus in the stools, and an ulcer in the rectum. The histopathological exam pointed to chronic, unspecified inflammation. After a broad serological screening, with Immunoglobulin M positive for Chlamydia and a high titer of immunoglobulin G, the patient was treated with antibiotics and is clinically cured. Later, he remained Immunoglobulin M positive, but the titers of immunoglobulin G lowered considerably. Chlamydia has been shown to live in the gut microbiota, which could explain the case. Conclusion: It is important to search for chlamydial infection as a differential diagnosis of ulcerative colitis.